Perceptions and beliefs of academic librarians in Germany and the USA: a comparative study - Kramer, Stefan; Horstmann, Wolfram (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
The purpose of this study is to understand, compare, and contrast professional experiences, perceptions, and beliefs among personnel in academic libraries in the USA and in Germany, which may inform future library and librarian collaborations between the two countries. Notable findings include differences in: respondents’ professional backgrounds; services offered by, and perceived adequacy and support of, respondents’ libraries; and views of the library profession and its future.